Transformation of Health and Social Care Systems—An Interdisciplinary Approach Toward a Foundational Architecture - Blobel, Bernd; Oemig, Frank; Ruotsalainen, Pekka; Lopez, Diego M. (Frontiers in Medicine, 2022)
For realizing pervasive and ubiquitous health and social care services in a safe and high quality as well as efficient and effective way, health and social care systems have to meet new organizational, methodological, and technological paradigms. The resulting ecosystems are highly complex, highly distributed, highly dynamic, following an inter-organizational and even international approach. Even when being based on international, but domain-specific models and standards, achieving interoperability between such systems integrating multiple domains managed by multiple disciplines and their individually skilled actors is cumbersome. Methods: Using the abstract presentation of any system by the universal type theory as well as universal logics and combining the resulting Barendregt Cube with parameters and the engineering approach of cognitive theories, systems theory and good modeling best practices, the paper argues for a generic reference architecture model moderating between the different perspectives the disciplines involved provide on that system. To represent architectural elements consistently, an aligned system of ontologies is used. Results: The system-oriented, architecture-centric, ontology-based generic reference model allows re-engineering existing and emerging knowledge representations, models and standards, also considering the real-world business processes and the related development process of supporting IT systems for the sake of comprehensive systems integration and interoperability. The solution enables analysis, design, and implementation of dynamic, interoperable multi-domain systems without requesting continuous revision of existing specifications.